Protective Effects of Middle School Comprehensive Sex Education With Family Involvement. (November 2014) - Grossman, Jennifer M.; Tracy, Allison J.; Charmaraman, Linda; Ceder, Ineke; Erkut, Sumru
ABSTRACT BACKGROUND School‐based comprehensive sex education programs can reduce early adolescents' risky sexual behavior. The purpose of this study was to assess the effectiveness of a 3‐year comprehensive sex education program in delaying vaginal sex for middle school students and whether the family component of the intervention contributes to its effectiveness. METHODS This longitudinal evaluation followed a cohort of 6th graders (N = 2453) through the end of 8th grade. The design used random assignment of 24 schools into treatment and comparison conditions. The analysis included multiple‐group logistic regression to assess differences in delay of sex between intervention and comparison groups. RESULTS In schools where the program was taught, 16% fewer boys and 15% fewer girls had had sex by the end of 8th grade compared to boys and girls at comparison schools. Completing family activities during the first year of the program predicted delayed sexual debut for boys. CONCLUSIONS Theory‐based, developmentally appropriate, comprehensive sex education programs that include parent involvement can be effective in delaying vaginal sex for middle school students. Parent involvement is particularly important for boys, as family activities may encourage parents to talk with their sons earlier and more frequently.